ALIH AKSARA DAN ALIH BAHASA TEKS HIKAYAT MIKRAJ RASULULLAH - Afrida, Winda; Zulfahdli, Zulfadhli (Universitas Negeri Padang, 2019)
This study aims to: (a) present the description of the text of the Hikayat Mikraj Rasulullah, (b) present the form of Arabic-Malay script transfer to the Latin script of the Hikayat Mikraj Rasulullah text, and (c) present the transitional form from Malay-Minang to Indonesian text The Story of Mikraj Rasulullah. This research is a philological research. The object of research is the text of the Hikayat Mikraj Rasulullah. The method used in this study is a philological method that is adjusted to the stage of the study. The results are (1) a complete description of the text of the Hikayat Mikraj Rasulullah. (2) the transfer of the text of the Hikayat Mikraj Rasulullah script from the Arabic-Malay script to the Latin script without changing the type of language that can be read and understood by the people of the present; (3) the transfer of the text of the Hikayat Mikraj Rasulullah text which has been adapted to Indonesian Spelling (EBI) . Some Malay and Minangkabau vocabularies found in the text of the Hikayat Mikraj Rasulullah have been retained to maintain the purity of the old vocabulary.